EVALUATION OF THE PROPERTIES MODIFICATION FOR VIA ENZYMATIC OF THE STARCH OF YAM (D. trífida) USING -AMILASA (TERMAMYL® 120 L, TYPE L) - MONTES M., Everaldo; SALCEDO M., Jairo; ZAPATA M., José E.; CARMONA C., Jesús; PATERNINA U., Sergio (Vitae, 2009)
The starch of yam constitutes an excellent raw material to modify the texture and consistency of foods. Its functionality depends on the molecular weight average of the amilosa and the amilopectina, as well as of the molecular organization of these glucanos within the grain, the native or natural starches are frequently not adapted for their use in some specific industrial processings. This investigation, one carries out the modification via enzymatic of the yam starch (D.trífida) using -amilasa (Termamyl 120L, type L of Novo Nordisk) to determine their functional properties. The established treatments for the enzymatic modification in this investigation are: reaction temperature (50, 72 and 93ºC), concentration of starch (30, 40 and 50% p/v) and time of reaction (20, 40 and 60 minutes). One carries out a design experimental factorial multinivel with four blocks. The starches hydrolysated at 93ºC show dextrose equivalent (DE) highest, followed respectively by those of 72 °C and 50ºC. The evaluated functional properties are: stability and clarity of the pasta, acidity titulable, swelling capacity, determination of the gelatinizatión point, true density, bulk density and porosity. This investigation demonstrate the great potential of the hydrolysates of starch of D. trífida like an alternative to respond to the demands of the industrial processes in the production of foods, such as bakery products, sauces, yogurts, marmalades and frozen products.